Single Dose of a VSV-Based Vaccine Rapidly Protects Macaques From Marburg Virus Disease - Marzi, Andrea; Jankeel, Allen; Menicucci, Andrea R.; Callison, Julie; O’Donnell, Kyle L.; Feldmann, Friederike; Pinski, Amanda N.; Hanley, Patrick W.; Messaoudi, Ilhem (Frontiers in Immunology, 2021)
Marburg virus (MARV) is a member of the filovirus family that causes hemorrhagic disease with high case fatality rates. MARV is on the priority list of the World Health Organization for countermeasure development highlighting its potential impact on global public health. We developed a vesicular stomatitis virus (VSV)-based vaccine expressing the MARV glycoprotein (VSV-MARV) and previously demonstrated uniform protection of nonhuman primates (NHPs) with a single dose. Here, we investigated the fast-acting potential of this vaccine by challenging NHPs with MARV 14, 7 or 3 days after a single dose vaccination with VSV-MARV. We found that 100% of the animals survived when vaccinated 7 or 14 days and 75% of the animal survived when vaccinated 3 days prior to lethal MARV challenge. Transcriptional analysis of whole blood samples indicated activation of B cells and antiviral defense after VSV-MARV vaccination. In the day -14 and -7 groups, limited transcriptional changes after challenge were observed with the exception of day 9 post-challenge in the day -7 group where we detected gene expression profiles indicative of a recall response. In the day -3 group, transcriptional analysis of samples from surviving NHPs revealed strong innate immune activation. In contrast, the animal that succumbed to disease in this group lacked signatures of antiviral immunity. In summary, our data demonstrate that the VSV-MARV is a fast-acting vaccine suitable for the use in emergency situations like disease outbreaks in Africa.